The comparison between internal determinat of conventional and Islamic banking profitability (Maybank and Bank Islam) / Nurul Hidayah Ab Rahman - Ab Rahman, Nurul Hidayah (2011)
Type of bank can be dividing by two which are conventional bank and Islamic bank. For this research study, the researcher chooses Malayan Banking Berhad (Maybank) as a conventional bank and Bank Islam Malaysia Berhad (BIMB) as a Islamic bank. The aim of this study was to examine the factors that influencing each bank profitability. There are 3 factors that been studied, which were Operating Expenses (OE), Credit Risk (CR) and Bank Siza (BS). This study also was conduct to identify which bank are the most preferred factors that influence to gain a profit. The period of study is from first quarter 2006 until fourth quarter 2010. Findings of the study show that Maybank as a conventional bank will got a great impact by all the factor chosen compare to Bank Islam. The research methodology use for this study is by using the secondary data from Quarterly Financial Statement report. Meanwhile, in analyzing the data the Statistical Procedure of Social System (SPSS) is being used in order to transfer the data into output. As a conclusion from the study, the finding of this study gives suggestion to the both bank to improve their internal factors to gain more profit